Targeting cellular senescence in cancer by plant secondary metabolites: A systematic review - Sajad Fakhri; Seyed Zachariah Moradi; Angela Ash-Rafzadeh; Anupam Bishayee (Elsevier, 2022)
Senescence suppresses tumor growth, while also developing a tumorigenic state in the nearby cells that is mediated by senescence-associated secretory phenotypes (SASPs). The dual function of cellular senescence stresses the need for identifying multi-targeted agents directed towards the promotion of cell senescence in cancer cells and suppression of the secretion of pro-tumorigenic signaling mediators in neighboring cells. Natural secondary metabolites have shown favorable anticancer responses in recent decades, as some have been found to target the senescence-associated mediators and pathways. Furthermore, phenolic compounds and polyphenols, terpenes and terpenoids, alkaloids, and sulfur-containing compounds have shown to be promising anticancer agents through the regulation of paracrine and autocrine pathways. Plant secondary metabolites are potential regulators of SASPs factors that suppress tumor growth through paracrine mediators, including growth factors, cytokines, extracellular matrix components/enzymes, and proteases. On the other hand, ataxia-telangiectasia mutated, ataxia-telangiectasia and Rad3-related, extracellular signal-regulated kinase/mitogen-activated protein kinase, phosphatidylinositol 3-kinase/Akt/mammalian target of rapamycin, nuclear factor-κB, Janus kinase/signal transducer and activator of transcription, and receptor tyrosine kinase-associated mediators are main targets of candidate phytochemicals in the autocrine senescence pathway. Such a regulatory role of phytochemicals on senescence-associated pathways is associated with cell cycle arrest and the attenuation of apoptotic/inflammatory/oxidative stress pathways. The current systematic review highlights the critical roles of natural secondary metabolites in the attenuation of autocrine and paracrine cellular senescence pathways, while also elucidating the chemopreventive and chemotherapeutic capabilities of these compounds. Additionally, we discuss current challenges, limitations, and future research indications.